2021
DOI: 10.3389/fgene.2021.710412
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Immune-Infiltrate Significance of miR-222-3p and Its Target Genes in Thyroid Cancer

Abstract: Thyroid cancer (THCA) is a common endocrine malignancy. With increasing incidence and low mortality, balancing the therapeutic approach is an inevitable issue. This study aimed to confirm the role of miR-222-3p and its target genes in THCA survival and immune infiltration. From different expression analyses based on the GEO and TCGA databases, we predicted and subsequently identified the key target genes of miR-222-3p. We then explored the expression, enrichment, pairwise correlation, protein expression, survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
2
6
0
Order By: Relevance
“…This is well in line with some previous reports demonstrating the up-regulation of miR-222, miR-221, and miR-146b in PTC patients compared to those with benign nodules and controls [ 23 , 24 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 45 ]. Rosignolo et al reported that the serum levels of circulating miR-221 were consistent with ATA responses to therapy in PTC patients, supporting their role in post-treatment monitoring [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This is well in line with some previous reports demonstrating the up-regulation of miR-222, miR-221, and miR-146b in PTC patients compared to those with benign nodules and controls [ 23 , 24 , 25 , 31 , 32 , 33 , 34 , 35 , 36 , 45 ]. Rosignolo et al reported that the serum levels of circulating miR-221 were consistent with ATA responses to therapy in PTC patients, supporting their role in post-treatment monitoring [ 25 ].…”
Section: Discussionsupporting
confidence: 93%
“…Overall, among the different serum miRNAs tested in our study, miRNA 221, 222, and 146b emerged as the most suitable candidate biomarkers to complement imaging (i.e., nUS, Dx-WBS) in the post-operative monitoring of PTC patients with uninformative Tg. This is well in line with some previous reports demonstrating the up-regulation of miR-222, miR-221, and miR-146b in PTC patients compared to those with benign nodules and controls [23][24][25][31][32][33][34][35][36]45]. Rosignolo et al reported that the serum levels of circulating miR-221 were consistent with ATA responses to therapy in PTC patients, supporting their role in post-treatment monitoring [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Next, we identified 4 intersection genes from m6Acluster types. XPNPEP2 was one of the critical genes in thyroid cancer targeted by miR-222-3p, [ 53 ] and it was associated with lymph node metastasis in prostate and cervical cancers. [ 54 , 55 ] REEP6, an accessory protein, refined CXCR1-mediated cellular responses in lung cancer.…”
Section: Discussionmentioning
confidence: 99%